Rediscovery of Portulaca trianthemoides (Portulacaceae) in southern Africa after 89 years - Woodenberg, Wynston R.; Govender, Yanadayalan; Ramdhani, Syd (Phytotaxa, 2024)
Portulaca trianthemoides was described in 1931 and known previously only from the type locality in Soutpansberg, Limpopo, South Africa. It has not been collected since 1934; however, a recent rediscovery of the species led us to investigate the name (typification) and propose an emended description. Some aspects of the ecology of the species are also discussed, and first images of live plants are provided. Despite its restricted distribution area, an estimation of the population size is more than c. 15,000 individuals, suggesting that the species is not of conservation concern.